Boreal climate change and its effects on Acid Sulfate Soils : The effects of drought on element mobilisation from acid sulfate soils - Bascunan, Daniel (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2025)
As the climate continues to become warmer, the effects of it become clearer. One of the effects of a warmer climate is the increase in drought events which have impacted several areas around the globe, especially in Europe in the last years. Drought can affect many things such as the water supply and the infrastructure, another area that can be affected by drought is acid sulfate (AS) soil. Usually covered by groundwater, when exposed to air the AS-soil starts oxidising, generating sulfate and mobilising metals which result in a lower pH and the increase of metals in the area surrounded by the AS-soil. A possible way to link drought to the release of AS-soil material is by analysing the sediment in areas close to AS-soil to see if it can be connected to a period of drought. This thesis will examine the changes in AS-soil release in northern Sweden over a 25-30 year period in relation to climate change by analysing and studying the sediment of the Lule River at Sunderby and from samples taken from the Baltic Sea. Due to the Baltic Sea cores being taken between 2003 and 2016, it was determined to limit the examined period to only 1973 and 2006. During this period, three droughts which occurred in northern Sweden could be identified, the 1974-1976 drought (Drought 3), the 1996-1998 drought (Drought 2) and the 2003 drought (Drought 1). Two sediment samples were extracted from Sunderby in February 2024 and seven sediment cores from the Baltic Sea were chosen to be analysed, with the analysis performed with a handheld XRF. The result from the analysis shows that the sediments from Sunderby did not appear to be affected by the surrounding AS-soil. The Baltic sediment cores displayed varied concentration at each location with the core closest to Umeå showing signs of being affected by AS-soil and one of the cores from Husum having high sulfur concentration. Due to the unknown sedimentation rate in the Lule river, the recent four years were examined to determine if drought affected the release of AS-material, in which it ...